Do the virtual water and water footprint perspectives enhance policy discussions? - Wichelns, Dennis (Informa UK Limited, 2011)
The notions of virtual water and water footprints are gaining popularity among researchers and practitioners in the eld of water resources. Many of the published articles include statements suggesting that public policies regarding water allocation, agriculture, or international trade should re ect consideration of virtual water and water footprints. Yet those notions lack a scienti cally tested conceptual framework and they are too narrowly de ned to inform policy decisions in a meaningful way. Consumers, rms, and public of cials wishing to improve water resource management need and deserve much better information than is contained in estimates of virtual water and water footprints. A more thoughtful, comprehensive approach is needed to develop policies that will truly improve the management of water and other natural resources, while also enhancing livelihoods.